Horizontal Pendulum Performance Analysis with Multilevel Model Plate on Ocean Wave Electric Power Plant (PLTGL) - Mukhtasor Mukhtasor; Tony Bambang Musriyadi; Irfan Syarif Arief; Ardika Wendy Cahya Saputra (International Journal of Marine Engineering Innovation and Research, 2017)
Abstract - With the times and the industry, the energy sources such as fossil fuels dwindling. It encourages all parties to be more advanced and developed by creating solutions to renewable energy generation with the latest innovations, one of which is the sea wave power plant - pendulum system. Ponton who uses pendulum system is one tool used to convert from ocean wave energy into electrical energy. In this study using the test conditions without using ballast onshore and off-shore testing with the ballasts. Obtained from testing the many rounds that can be generated pendulum pie plate thickness and the angle of the pontoon. To test the largest on-shore power obtained on the test using arc angle 30 °, 3 mm thick, the angle of 60o power produced 0036 watts. For testing offshore in the ballasts 12 cm, 15 cm, 17.5 cm, the largest power generated at 15 cm ballasts with 0041 watts power on pie, thick, and a tilt angle equal to the on-shore testing. Number of rounds with time, the on-shore testing that produces the greatest value in the segment with an angle of 30 °, a thickness of 3 mm the angle of 60o value obtained 0.938 rad / s. In the off-shore pengjuain is greatest in the ballasts 15 with 0847 rad / s.